Differences in Dropout Rates by Ethnicity/Race of Middle School Students: A Multi-Year Analysis (Global Journal of Human-Social Science, 2016)
Examined in this study were dropout rates for Black, Hispanic, and White middle schools students during the 2012-2013 and 2013-2014 school years. Texas middle school dropout rates were downloaded from the Texas Academic Performance Reports for two school years. Inferential statistical analyses were conducted separately for each ethnic/racial group to determine whether changes had occurred in their dropout rates between the 2012-2013 and 2013-2014 school years. Black and White students did not have a statistically significant difference in their dropout rates between those two school years. Hispanic students, however, had a statistically significantly higher dropout rate in the 2013-2014 school year than in the 2012-2013 school year. Implications of these results are discussed, as well as recommendations for future research.
Keywords: dropout rates; texas academic performance report; black; hispanic; white